2006
DOI: 10.1002/ana.20852
|View full text |Cite
|
Sign up to set email alerts
|

How long does it take for epilepsy to become intractable? A prospective investigation

Abstract: Intractable epilepsy may be delayed, especially in focal epilepsy. It often is preceded by a quiescent period, followed by further remissions. These findings help explain why surgically treatable epilepsies may take 20 years or longer before referral to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
172
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 37 publications
12
172
0
7
Order By: Relevance
“…In our study this was also one of the most influential risk factors for drug-resistant epilepsy (Cramer's V = 0.62). This view is shared by most authors [6,8,13,22,25]. According to Camifield, normal intellectual development is fundamental for good prognosis in epilepsy [26].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study this was also one of the most influential risk factors for drug-resistant epilepsy (Cramer's V = 0.62). This view is shared by most authors [6,8,13,22,25]. According to Camifield, normal intellectual development is fundamental for good prognosis in epilepsy [26].…”
Section: Discussionmentioning
confidence: 95%
“…The most frequently mentioned clinical factors include the following: initial antiepileptic treatment [6,7], considerable initial frequency of epileptic seizures [6,[8][9][10][11][12], occurrence of status epilepticus [6,[13][14][15][16][17], symptomatic aetiology of epilepsy [6,16,18], type of epilepsy/epileptic syndrome [11,13,14,16,[19][20][21][22], onset of epileptic seizures before the first birthday [13,15,18,23,24], abnormal results of neurological examination [8,18,23,24,25], and abnormalities detected in imaging [18,23] and EEG examinations [15,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, memory loss, learning disabilities, and behavioral problems are especially common in epilepsy patients, and often exhibit a progressive course, frequently correlating with worsening seizure control [1][2][3][4][5]. Furthermore, about one-third of all patients with epilepsy have seizures that are intractable to all currently-available treatments and that may escalate in frequency and severity [6][7][8]. There are multiple biological, environmental, and psychosocial factors that may contribute to progressive neurological dysfunction in epilepsy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite appropriate treatment with antiepileptic drugs, seizures persisted in approximately 20 and 35% of patients with primary generalized epilepsy and those with partial epilepsy, respectively [5]. A recent study demonstrated that up to 23% of epilepsy cases were intractable, if intractability was defined as failure of two drugs [6]. For patients with intractable seizures, other methods of treatment including surgical treatment should be considered.…”
Section: Introductionmentioning
confidence: 99%